‘We Are Not Bad People’- Bricolage and the Rise of Community Forest Institutions in Burkina Faso - Karambiri, Mawa; Brockhaus, Maria; Sehring, J.; Degrande, A. (Ubiquity Press, Ltd., 2020)
From a critical institutionalism and institutional bricolage perspective, this article analyses what drives institutional change in the commons and the outcomes for forest and people. It builds on the comparison of three neighbouring villages in Burkina Faso that in 1989, expecting higher returns, agreed to release their common lands for the creation of a community forest called Chantier d’Aménagement Forestier (CAF) within an international forestry project. The project created new bureaucratic institutions to replace the pre-existing customary and socially embedded system. Decades later, the three villages display different institutional change pathways and outcomes: one village abandoned the CAF, converted, and sold its forest and land; another maintained the CAF; and a third operates in-between. Using qualitative research methods, we ask why and how these different change trajectories and outcomes occurred among villages of identical cultural and sociopolitical background. The results show that poor design and implementation of the new bureaucratic institutions, as well as their disrespect of customary and socially embedded rules, led to forestland disputes between the villages. The bureaucratic institutions failed to solve those disputes, effectively manage the forest, and share the benefits equitably. This caused local people’s discontent and prompted actions for change. Actors in diverse ways made use of their social networks, agency, and power relations within and between the villages to either reshape, re-interpret or reject the new forest institutions. These processes of institutional bricolage led to highly diverse trajectories of change. The findings demonstrate the crucial role of locals as agents of change from below and question universal claims in institutional theory on how institutions induce rule-guided behaviour and create path dependencies.